Perancangan Sistem Informasi Pendataan Penduduk Desa Bedulu Kecamatan Blahbatuh Kabupaten Gianyar - Darma Wijaya, I Putu Eka (JATISI, 2025)
The population administration system is a vital component of government operations, managing population data that includes essential demographic information. However, many villages, including Bedulu Village, still rely on manual methods for recording population data, which are prone to errors, data duplication, and security issues. According to an interview with the Head of Bedulu Village, it was noted that this manual process presents challenges such as the potential for data loss or damage and the inability to ensure accurate population counts. Therefore, this study aims to design a computerized population data management system to replace the manual methods with a more efficient and accurate digital solution. The system is designed to record data in real-time, minimize the potential for data loss or damage, and avoid data duplication. This study adopts an Agile approach to system development, as this method has proven effective in delivering systems that meet user needs and enhance user satisfaction. Agile focuses on rapid and adaptive progress, with active user involvement throughout the development phase. With the implementation of this computerized information system, it is expected that Bedulu Village will be able to manage population data more effectively, improve the quality of public services, and better support government programs. Keywords: Population information system, Agile, Bedulu Village, computerized data management, public services.